Violent Crime as Urban Security Problem - Paraušić, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Contemporary cities represent areas of significant contradictions. On the one hand, they are a source of prosperity, innovation and opportunities, and on the other stages of various security problems. One of the most frequently and traditionally studied security problems in cities is violent crime in the urban environment. Bearing in mind the importance of violent crime in the study of urban security, we will try to give holistic insights into this security problem in urban areas. First, the basic manifestations of violent crime, as well as various theoretical explanations of its causes, are presented. Secondly, some of the theoretical assumptions about urban violent crime are addressed. Thirdly, some synthetic insights about the characteristics and specifics of violent crime as a problem of urban security are provided. In the end, it is important to summarize the consequences that urban violent crime has on the life and well-being of individuals and families, the quality of neighborhood and local communities, as well as on urban governance.